2016
DOI: 10.1590/s1806-37562016000000057
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function in children and adolescents with sickle cell disease: have we paid proper attention to this problem?

Abstract: Objective:To evaluate pulmonary function and functional capacity in children and adolescents with sickle cell disease. Methods:This was a cross-sectional study involving 70 children and adolescents (8-15 years of age) with sickle cell disease who underwent pulmonary function tests (spirometry) and functional capacity testing (six-minute walk test). The results of the pulmonary function tests were compared with variables related to the severity of sickle cell disease and history of asthma and of acute chest syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
1
8
0
1
Order By: Relevance
“…These findings underscore the need for the recognition of asthma, as well as the importance of longitudinal follow‐up of pulmonary function, in this population . This may also indicate that several inflammatory mechanisms are involved in the genesis of airway obstruction in SCD …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings underscore the need for the recognition of asthma, as well as the importance of longitudinal follow‐up of pulmonary function, in this population . This may also indicate that several inflammatory mechanisms are involved in the genesis of airway obstruction in SCD …”
Section: Discussionsupporting
confidence: 89%
“…Recently, Vieira et al evaluated pulmonary function in 70 children and adolescents with SCD. Of the 64 patients who underwent spirometry, 8 (12.5%) showed restrictive lung disease and 7 (10.9%) had OLD.…”
Section: Discussionmentioning
confidence: 70%
“…Complementando o estudo 5, a pesquisa de número 11 identifica um prejuízo na ventilação pulmonar nas crianças portadoras de asma, quando comparadas com crianças sem a enfermidade, o achado se concretiza através de exames de imagem como ressonância magnética de gás hiperpolarizado, estando o comprometimento associado a gravidade da asma (de caminhada de 6 minutos, foi utilizado nesta pesquisa, buscando correlacionar a dessaturação como diagnóstico precoce também para hipertensão pulmonar. O estudo identificou ainda que há relação entre anormalidade da função pulmonar e os valores de saturação, podendo indicar doença pulmonar crônica na presença de doença falciforme (Vieira et al, 2016).…”
Section: Resultados E Discussõesunclassified
“… 8 It was also demonstrated that patients with PH (including those with postcapillary PH) have reduced exercise tolerance, despite having preserved or even increased cardiac output. In the study conducted by Vieira et al, 7 the lack of echocardiographic evaluation constitutes a limitation that precludes the identification of other factors associated with desaturation. In patients with high-output PH, increased pulmonary flow can lead to diffusion/perfusion mismatch enhanced by a rightward shift of the hemoglobin dissociation curve and associated V• //Q mismatch ( Figure 1 ).…”
mentioning
confidence: 99%
“…In the previous issue of the JBP, Vieira et al 7 evaluated children and adolescents with sickle cell disease using spirometry and the six-minute walk test. It is of note that changes in gas exchange during exercise were common in the study sample: 52% had a significant decrease in SaO 2 as assessed by pulse oximetry (SpO 2 ) at the end of the six-minute walk test.…”
mentioning
confidence: 99%